The effect of climate on the choice of wool based fabric. - Banfield, Gregory J. (Curtin University, 1999)
The research question addressed in this study is "what outerwear fabric types are preferred by consumer segments in each of the major climatic zones in Australia?" objectives are to:1. examine consumer preference for fabric in each of the five major climatic zones in Australia, using fabric attribute levels as the choice criteria, in order to provide information to Stormboy on fabric attributes most preferred by consumers, and the market segments in each zone, based on these fabric attribute preferences; and2. determine any significant differences in fabric preference between the climatic zones so as to indicate to Stormboy whether climate should be taken into consideration in the marketing of wool based fabric.This information on preference for fabric type, will enable Stormboy design wool based fabrics that match the fabric attribute requirement of consumers. The information on market segments will not only provide the fabric attribute requirements but also the possible size of the market.This study will develop a method to monitor consumer trends in fabric preference so that Stormboy can make informed decisions about their design and choice of wool based fabric.This study provides the required consumer information to Stormboy. It illustrates a method of research which can be used in decisions making by producers of products or services where there is heterogeneity in buyers' preferences, for:the development of new products or services;the renewal of a product or service;the positioning of a product or service; andthe ongoing monitoring of consumer preferences and retail compatibility with consumer preferences.As Green and Kreiger (1985) conclude, once preference and segments have been identified companies can react to (or possibly produce to) preference heterogeneity by modifications of their current product/service attributes (including price), distribution, and advertising/promotion. Companies are motivated to do so if the net payoff from modifying their offerings exceeds what the payoff would be without such modification. Companies may modify its product/marketing mix to include product line addition/deletion decisions as well as the repositioning of current offerings.The study begins by reviewing relevant literature on the function of clothing and fabric type, the position of wool in the apparel market, the effect of climate on choice, the key concepts of consumer behaviour and segmentation as a means of positioning products. The design of the research is summarised in Chapter 3, and the findings from a survey of consumers in five Australian centres are presented in Chapter 4. Chapter 5 discusses the implications of these findings and recommendations made to StormBoy. Conclusions relating to the study design, limitations and future research are addressed in Chapter 6.